Assessment of COVID-19 impact on commercial sex workers in India: A formative research by media scanning - Nupur Mahajan; Simran Kohli; Sumit Aggarwal (Wolters Kluwer Medknow Publications, 2023)
Background: The COVID-19 pandemic restricted movement, closed businesses, and economic activities which disproportionately affected people globally. This pandemic has resurfaced the existing cracks in the societal set-up and has pushed the vulnerable and marginalized communities like migrant workers, people with disabilities, geriatric population, and commercial sex workers (CSWs) to an edge for their existence. Materials and Methods: Due to the paucity of peer-reviewed research publications on CSWs, formative research was conducted to identify the determinants and attributes of the challenges faced by CSWs during COVID-19 situation in India. Media scanning approach was used to collate literature from newspaper and magazine reporting, and peer-reviewed articles were referred from research-based search engines. Results: In total, 31 articles were included for content analysis and four domains of issues i.e., economic, social, psychological and health related challenged faced by them were identified which are supported with the verbatims of the community members as reported in the data sources considered for this study. It was identified that the CSWs adopted several protective measures and coping strategies to deal with the pandemic situation. Conclusion: This research highlighted that there is a need for further exploration of issues among CSWs by conducting studies among the communities. Furthermore, this paper provides a scope for future implementation research by identifying the key priorities and determinants of the challenges among the personal livelihood of CSWs in the country.